(untitled) (Journal of Applied Learning and Teaching, 2025)
Green education as mentioned in Thakur S. Powdyel’s My Green School: An Outline (2014) was developed to support democratic Bhutan’s initiative ‘Educating for Gross National Happiness’ (EGNH), pinned on the nature-culture axis. The initiative motivated the educational institutions to imbue their teaching-learning environment with the values of Gross National Happiness (GNH). However, in terms of holistic development in modern education, the concept requires an integrated understanding beyond the explicit meaning of green, which primarily denotes nature and the environment. The eight dimensions of green school, denoted by the term ‘Sherig Mandala’ and designed in a concentric sense, hold a critical significance. Besides dealing with the idea of education through the natural environment, the concept also has a major claim on an individual’s life and learning on a moral level, integrating the physical and psychosocial ambience. It attempts to establish that the process of learning is the key to understanding the principles of life. With the core value of education being jeopardized in modern times, the paper attempts to ascertain the meaning and purpose of learning for a holistic life. The inherent meanings of the elements of greenery such as natural, social, cultural, intellectual, academic, aesthetic, spiritual and moral were examined to comprehend their philosophical intent. The significance of the concept was examined not in isolation but in correlation with the nine domains of Bhutan’s developmental philosophy known as GNH. Further, the paper has also affirmed that the conceptualization of ‘Green School’ in Bhutan is quite different from other countries around the world because it focuses not on the buildings and infrastructure, but on the behaviour and the core inner aspects that each child requires. This is to emphasize the fact that only the nobility of mind, heart and hands would empower the learners.